2019
DOI: 10.3103/s1063457619020035
|View full text |Cite
|
Sign up to set email alerts
|

Deposition and Characterization of Thin Si-B-C-N Films by DC Reactive Magnetron Sputtering of Composed Si/B4C Target

Abstract: Deposition and characterization of thin Si-B-C-N films by dc reactive magnetron sputtering of composed Si/B 4 C targetThe effect of the gas mixture composition on the structure, chemical bond character and hardness of Si-B-C-N films was systematically studied. A series of Si-B-C-N films was deposited by reactive dc magnetron sputtering of the target composed of Si disc with B 4 C chips placed in the sputtering zone of disc. The films were deposited with nitrogen fractions 30-to-70 % in Ar/N 2 gas mixture and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The interaction between Fe and B was first investigated by X‐ray photoelectron spectroscopy (XPS). The deconvoluted B 1s signals of 0.3Fe‐BNC revealed the coexistence of B–N (≈192.0 eV) and B–C (≈190.9 eV) bonds; [ 12 ] while, the B─B (≈188.0 eV) and B─Fe bonds (≈188.4 eV) were absent, [ 13 ] underlining that B was isolated without coordinating with Fe ( Figure a). In the N 1s XPS spectrum of 0.1Fe‐NC (Figure 2b; Table S2, Supporting Information), the peaks centered at 398.4, 399.2, 400.4, and 401.1 eV were assigned to pyridinic N, Fe–N, pyrrolic N, and graphitic N, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The interaction between Fe and B was first investigated by X‐ray photoelectron spectroscopy (XPS). The deconvoluted B 1s signals of 0.3Fe‐BNC revealed the coexistence of B–N (≈192.0 eV) and B–C (≈190.9 eV) bonds; [ 12 ] while, the B─B (≈188.0 eV) and B─Fe bonds (≈188.4 eV) were absent, [ 13 ] underlining that B was isolated without coordinating with Fe ( Figure a). In the N 1s XPS spectrum of 0.1Fe‐NC (Figure 2b; Table S2, Supporting Information), the peaks centered at 398.4, 399.2, 400.4, and 401.1 eV were assigned to pyridinic N, Fe–N, pyrrolic N, and graphitic N, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…This finding confirms that the size of the bombarded target particles gradually increases with increasing sputtering power, eventually leading to the deposition of film grains on the substrate. These larger particle clusters could be graphite clusters, nitride, and boride particles [ 14 ]. The cross-sections of the films are smooth and without obvious defects, and the demarcation line between the layers is not obvious owing to the gradient film preparation method applied.…”
Section: Resultsmentioning
confidence: 99%
“…J. Vlček et al [ 13 ], for example, deposited amorphous Si-B-C-N films with smooth surfaces on SiC and Cu floating substrates and showed that the films had an elastic recovery of 75% with suitable optical transmittance and oxidation resistance. Onoprienko A A et al [ 14 ] prepared Si-B-C-N films with controlled N contents and high hardness by DC reactive magnetron sputtering; the authors’ results [ 15 ] revealed the potential of B-C-N synergy in the design of new materials with enhanced properties.…”
Section: Introductionmentioning
confidence: 99%